"Between Two and Four": The French Initiative and the Multi-Power Diplomatic Initiatives to Resolve the Middle East Crisis. Issue 1 (2nd January 2016) - Blanga, Yehuda U.
ABSTRACT: This analysis examines one of the unknown chapters in the diplomatic history of the Arab-Israeli conflict: the French initiative of 1969 calling for diplomatic co-operation amongst the four Great Powers—the United States, Soviet Union, Britain, and France—to put an end to the conflict. The "Forum of Four" did not just attempt to mediate and achieve a compromise between Israel and the Arabs; it also presumed to define the general envelope for the agreement and dictate the path that the sides should follow toward a peace agreement. This analaysis examines the diplomatic positions of Israel, Egypt, and their superpower patrons—which conducted a "Forum of Two"—during the first months of the War of Attrition in 1969 and presents the details of the planned agreement worked out in the deliberations amongst the Powers, especially the United States and Soviet Union. It also surveys the reactions to them and the reasons why mediation failed.